(untitled) (Global Journal of Science Frontier Research, 2023)
The paper outlined an effective method for curing tobacco which includes the combined action of a microwave electromagnetic field and light with a wavelength of 400- 700nm The developed method made it possible to obtain tobacco material with high taste and moderate speed The high efficiency of the proposed method has been proven by IR and X-ray photoelectron spectroscopy